Split phenomena in amyotrophic lateral sclerosis: Current evidences, pathogenetic hypotheses and diagnostic implications - Zoccolella, Stefano; Giugno, Alessia; Logroscino, Giancarlo (Frontiers in Neuroscience, 2023)
Amyotrophic lateral sclerosis (ALS) is the most common motor neuron disease and has emerged among the disorders with the largest increasing incidence in Western countries. Although the diagnosis is based on clinical ground, electromyography and nerve conduction studies play a crucial role to exclude other potential etiologies of lower motor neuron dysfunction. Based on clinical grounds, a peculiar pattern of dissociated atrophy of the intrinsic hand and foot muscles, termed the 'split hand' and ‘split-leg’ signs, has been described in a significant proportion of cases with ALS, even at the early stages of the disease, when symptoms are focal. These signs are rare in neurological and non-neurological diseases other than ALS. In this review, we discussed current evidences concerning split-hand and split-leg signs, their clinical implications and neurophysiological findings. We also analyze whether split-hand and split-leg signs can be reliable markers in the differential diagnosis and in prognosis of ALS.